Highly active recyclable SBA-15-EDTA-Pd catalyst for Mizoroki-Heck, Stille and Kumada C-C coupling reactions - Rathod, Jayant; Sharma, Priti; Pandey, Punam; Singh, A. P.; Kumar, Pradeep (Journal of Porous Materials, 2017)
Highly efficient SBA-15-EDTA-Pd(11) heterogeneous catalyst was synthesized by covalent anchoring Pd-EDTA complex over organo-modified surface of SBA-15. SBA-15-EDTA-Pd(11) catalyst was found to exhibit excellent catalytic activity in appreciable yield for Heck, Stille and Kumada cross-coupling reactions. Catalytic system exhibited excellent activity for completion of reaction, isolation, Pd loading (0.87 mmol%) and yields of products as compared to earlier reported heterogeneous supported Pd catalysts. Covalently anchored heterogeneous SBA-15-EDTA-Pd(11) catalyst can be recycled for more than five times without noticeable loss in activity and selectivity.

Harnessing nucleophilicity of allenol ester with p-quinone methides via gold catalysis: application to the synthesis of diarylmethine-substituted enones - Sharma, Brijesh M.; Rathod, Jayant; Gonnade, Rajesh G.; Kumar, Pradeep (Journal of Organic Chemistry, 2018)
A gold(I)-catalyzed protocol for intermolecular 1,6-conjugate addition of nucleophilic allenol ester generated in situ through [3,3]-sigmatropic rearrangement with p-quinone methides (p-QMs) has been developed. The gold catalyst plays a dual role by the pi-acid-triggered activation of alkynes and at the same time as a Lewis acid for activation of p-QMs toward nucleophilic attack. This method enables rapid access to a wide range of densely functionalized diarylmethine-substituted enones, a Morita-Baylis-Hillman (MBH) product with high selectivity, excellent yields, and broad substrate scope.